2023
DOI: 10.1108/ijcma-03-2023-0038
|View full text |Cite
|
Sign up to set email alerts
|

Service with a sense of belonging: navigating work–family conflict and emotional irritation in the service efforts of health professionals

Abstract: Purpose The service effort behavior (SEB) of health professionals may be impeded by many factors. This study aims to draw upon the conservation of resources and stressor–strain–outcome theories to test a moderated mediation model that explores how work–family conflict (WFC) influences SEB. The mediating effect of emotional irritation (EI) and the moderating effect of organizational identification (OI) was also tested. Design/methodology/approach Data was collected over two waves from 524 health professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…In addition, this study observed that burnout, to some extent, mediates the relationship between work-family conflict and turnover intention, and the mediating effect is significant. Although there had been studies exploring the relationship between turnover intention, burnout, and work-family conflict, there was limited research literature on the three factors mentioned above among primary medical staff, and there was even more limited research on the role of burnout in the relationship between work-family conflict and turnover intention ( 41 45 ). Therefore, attention needs to be paid to work-family conflict, burnout, and turnover intention among primary medical staff ( 46 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study observed that burnout, to some extent, mediates the relationship between work-family conflict and turnover intention, and the mediating effect is significant. Although there had been studies exploring the relationship between turnover intention, burnout, and work-family conflict, there was limited research literature on the three factors mentioned above among primary medical staff, and there was even more limited research on the role of burnout in the relationship between work-family conflict and turnover intention ( 41 45 ). Therefore, attention needs to be paid to work-family conflict, burnout, and turnover intention among primary medical staff ( 46 48 ).…”
Section: Discussionmentioning
confidence: 99%